Topology synthesis and control of integrated three-port converter for renewable energy system. (July 2022) - Senapati, Laxmidhar; Garg, Man Mohan; Panda, Anup Kumar; Lenka, Rajesh Kumar
Highlights: Only three switches are included in the proposed TPCC. In any mode of operation, one or two switches are working. The number of semiconductor devices is less than the existing topology, reducing costs and increasing power density. Two independent control loops can be obtained by using a decoupled network to achieve the optimized control for the proposed converters, which helps to simplify the control loop design. A PI-Lead compensator is used in the controller to achieve improved steady-state and transient performance in each operating mode. The AMS technique is proposed to achieve a seamless transition among different operating modes. Abstract: This paper presents topology synthesis and control of a non-isolated three-port dc-dc Cuk converter (TPCC) for a renewable energy system (RES). The proposed control structure is composed of a decoupling network to address the inevitable cross-coupling effect of multiport converters present due to various interacting control loops. In addition, a PI-lead compensator is designed to achieve improved steady-state and transient performance in each operating mode of TPCC. Furthermore, an autonomous mode selection (AMS) technique is proposed to achieve a seamless transition between different operating modes. The AMS technique automatically shifts the operating modes of TPCC by comparing the available instantaneous power at each port to maintain an uninterruptable power supply to the load. Moreover, a state-space averaging method is adopted for modeling different operating modes and transfer functions of TPCC. Finally, the feasibility and effectiveness of the proposed control algorithm are validated with the help of a laboratory prototype. Graphical abstract: Proposed three port Cuk converter topology. Image, graphical abstract